Management of human epidermal growth factor receptor inhibitors-related acneiform rash: a position paper based on the first Europe/USA Delphi consensus process - Apalla, Zoe; Freites-Martinez, A.; Grafanaki, K.; Ortiz-Brugues, A.; Nikolaou, V.; Fattore, D.; Sollena, P.; Deverapalli, S.; Babakoohi, S.; Galimont, A.; Kluger, N.; Beylot-Barry, M.; et al. (Journal of the European Academy of Dermatology and Venereology, 2025)
BACKGROUND: There is a need for unified guidance in the management of acneiform rash induced by epidermal growth factor receptor inhibitors (EGFRi) among dermatologists. - OBJECTIVE: To establish unified international guidelines for the management of acneiform rash caused by EGFR inhibitors, based on an experts' Delphi consensus. - METHODS: The initiative was led by five members of the European Academy of Dermatology and Venereology Task Force 'Dermatology for Cancer Patients' who developed a questionnaire that was circulated to a group of 32 supportive oncodermatology experts in Europe, Canada, Argentina, the US States and Asia. The questionnaire consisted of 84 statements in total, regarding diagnosis and treatment of EGFRi-induced acneiform rash. Experts responded to an anonymous 5-point Likert scale survey. The coordinators collected the first-round responses that were checked for consensus (≥75% agreement in positive [agree or strongly agree] or in negative [disagree or strongly disagree] vote). The statements that did not reach strong consensus in the first round were revised, according to experts' feedback, for a second-round survey. - RESULTS: Strong consensus was reached in 75/84 (89.3%) of the statements, whilst moderate consensus was achieved in 6/84 elements. Key points include consideration of low-dose isotretinoin for refractory grade II/III acneiform rash, use of topical steroid-sparing agents like topical pimecrolimus in the maintenance phase and use of doxycycline in either 100 or 200 mg per day as prophylactic treatment. Interestingly, experts did not recommend topical antibiotics, neither for prevention, nor for treatment. Consensus failure in 3/84 objects is mostly related to the lack of robust data on these topics. - CONCLUSION: This consensus offers crucial insights often overlooked by radiotherapists, general practitioners, dermatologists and oncologists, and it is expected to improve the management of oncologic patients treated with EGFRi in different settings and continents.
Online veröffentlicht: 26 October 2024
Gesehen am 19.08.2025